Study on the prevalence of diabetic retinopathy in Pudong New Area and the predictive value of estimated glucose disposal rate: a cross-sectional study - Gao, Jiaojiao; Wu, Kang; Wang, Xiaonan; Li, Zhitao; Liu, Xiaolin; Song, Jiahui; Liu, Yang; Qiu, Hua; Wei, Feng; Xu, Qian; Xiao, Shaotan; Zhou, Yi; et al. (Frontiers in Endocrinology, 2025)
ObjectiveTo describe the prevalence of diabetic retinopathy (DR) in patients with type 2 diabetes mellitus (T2DM) in Pudong New Area, Shanghai, and to explore the association between estimated glucose disposal rate (eGDR) and DR, as well as the possibility of eGDR as a predictive marker.MethodsField investigation was conducted among sampled patients with T2DM from May to September 2023. Fundus examination was performed by automatic mydriatless fundus camera to evaluate the prevalence of DR. Restricted cubic spline (RCS) function was employed to evaluate the dose-response relationship between eGDR and DR. Logistic regression analysis was performed to examine their association.ResultsA total of 2,327 patients with T2DM completed the survey, with a median age of 69 years. The prevalence of DR in Pudong New Area was 7.39%, and RCS curve demonstrated a significant negative linear relationship between eGDR and DR. After controlling for confounding factors, the results of the logistics regression showed that the risk of DR decreased by 40.4% for every one standard deviation increase in eGDR. The area under the ROC curve for eGDR predicting DR was 0.777 and 0.781, indicating a high predictive value of eGDR for DR.ConclusionThere is a significant negative linear association between eGDR and the risk of DR, and eGDR is expected to serve as a target for DR prediction and intervention.